A Systematic Review of Pressure Ulcers Prevention - Wahyuni, Erna Dwi; Dewi, Yulis Setiya; Laili, Nadia Rohmatul; Kurniawati, Ninuk Dian; Wulandari, Sartika; Gunawan, Gunawan; Lestari, Diah (Fundamental and Management Nursing Journal, 2023)
Introduction: Pressure ulcers in high-risk patients are contributes to patient burden and cost financially. Identifying strategies on the prevention of high ulcers among those with high risk is necessity. Nevertheless, an intense study exploring those issues is scarce. The study aimed to analyze the prevention method and their effectiveness in pressure ulcer prevention. Method: This study used PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) to guide the systematic review process. The article searches were conducted on Web of Science (WOS), ScienceDirect, Wiley Online Library, and Scopus using the keywords used Decubitus Ulcer, Pressure Ulcer, Management, and Prevention, and any possible combinations. Results: A total of 18 studies met the inclusion criteria for this review and show some different prevention for a pressure ulcer. The findings of the present study are foam dressings, support surfaces, repositioning, topical-based interventions, wearable patient sensors, and two distinct endotracheal tube fixations affect the incidence of pressure ulcers. Conclusions: This current review emphasized a bundle care consisted of two methods or more are effective to reduce the incidence of pressure ulcers rather than a single treatment. Nurses should consider intervention to prevent ulcers among high-risk patients by way analyses of each single treatment prior bundling. Further study investigating factors associated wound's ulcer healing is necessary.